2017
DOI: 10.1038/s41535-017-0044-5
|View full text |Cite
|
Sign up to set email alerts
|

Metallicity without quasi-particles in room-temperature strontium titanate

Abstract: Cooling oxygen-deficient strontium titanate to liquid-helium temperature leads to a decrease in its electrical resistivity by several orders of magnitude. The temperature dependence of resistivity follows a rough T 3 behavior before becoming T 2 in the lowtemperature limit, as expected in a Fermi liquid. Here, we show that the roughly cubic resistivity above 100 K corresponds to a regime where the quasi-particle mean-free-path is shorter than the electron wave-length and the interatomic distance. These criteri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 70 publications
(109 reference statements)
6
37
0
Order By: Relevance
“…α in µ ∼ n −α is close to unity). Second, this mobility is strongly temperature dependent and passes from a room-temperature value of 5 cm 2 V −1 s −1 to 20000 cm 2 V −1 s −1 at liquid He temperature [40,41]. This latter value implies that the low-temperature carrier mean-free-path becomes much longer than the interdopant distance (l ee = n −1/3 ) in contrast to the ionized-impurity-scattering scenario.…”
Section: Resultsmentioning
confidence: 96%
“…α in µ ∼ n −α is close to unity). Second, this mobility is strongly temperature dependent and passes from a room-temperature value of 5 cm 2 V −1 s −1 to 20000 cm 2 V −1 s −1 at liquid He temperature [40,41]. This latter value implies that the low-temperature carrier mean-free-path becomes much longer than the interdopant distance (l ee = n −1/3 ) in contrast to the ionized-impurity-scattering scenario.…”
Section: Resultsmentioning
confidence: 96%
“…On the other hand, Spinelli et al [251] estimated values for a H of 200 nm at RT and as large as 10 µm for low temperatures, where ε is enhanced by two orders of magnitude. To cope with the very low value of the carrier concentration limit in the case of the classical interpretation of the insulator-to-metal transition for SrTiO 3 other authors have suggested resolving the contradiction by applying, e.g., the Mott-Ioffe-Regel (MIR) limit [252]. This model can be used when the mean-free-path of a carrier falls below its Fermi wavelength or the length is smaller than the lattice constant (interatomic distance).…”
Section: Electrical Properties Of the Dislocations In Tio 2 And Srtiomentioning
confidence: 99%
“…Thus, the two features are independent phenomena. Bulk SrTiO 3 has an antiferrodistortive transition at ∼110 K, and resistance anomalies have been observed to be associated with it [21][22][23], although their precise origin remains to be determined. Figure 3 shows T MIT as a function of the sheet carrier density (n s ), determined at room temperature from the Hall measurements (shown in Fig.…”
mentioning
confidence: 99%